FAKTOR-FAKTOR KEBERHASILAN BADAN EKSEKUTIF MAHASISWA TELKOM UNIVERSITY - Pangarso, Astadi; Syahputra, Syahputra; Seto Perbowo, Grahatama Windhu (Jurnal Ekonomi Modernisasi, 2016)
Telkom university is private universitiy under telkom foundation. Student organisation are the ones consisted of college students to accommodate talent, interest and potential student who conducted at the extracurricular activities .The purpose of this research to know variable the most dominant of organisation factors success based the theory of schmuck .This research using 110 sample of the local the executive agency students telkom university , data collection use questionare .The kind of research this is descriptive analysis by approach quantitative. The analysis used is Confirmatory Factor Analysis (CFA). This research result indicates factors most dominant is a factor clarifying communication , on the dominant seven indicators that affects , the most dominant are the delivery of information about an event pertaining to work programs BEMÂ  fast.